(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
Blepharospasm is any abnormal contraction or twitch of the eyelid. the condition should be distinguished from the more common, and milder, Involuntaryquivering of an eyelid, known as myokymia. Benign essential blepharospasm (BEB) is craniofacial dyskinesia characterized by repeated, involuntary contractions of the orbicularisoculi, procerus, and corrugator muscles. The mechanism underlying benign essential blepharospasm is not yet clearly understood but is thought to be multifactorial, with a likely genetic component and an environmental trigger. It has been suggested that BEB may be partly due to abnormalities in the basal ganglia and dopaminergic system involving a subclinical loss of striatal dopamine.